Perforated primary intestinal lymphoma: Case report - Tartar, Tugay; Sari, Mehmet Yusuf; Dagli, Adile Ferda; Saraç, Mehmet; Bakal, Ünal; Kazez, Ahmet (Logos Medical Publishing, 2020)
Primary gastrointestinal system (PGIS) lymphomas are rare. It is very difficult to diagnose PGIS lymphoma preoperatively.A 3-year-old male patient with an intraabdominal mass was presented in this study. Lymphoma was considered as the preliminary diagnosis. Fine-needle biopsy was performed, and pathological examination of the biopsy specimen showed CD20 (+) aggressive B-cell lymphoma. Intestinal perforation developed on the third day of chemotherapy, and emergency laparotomy was performed. Colon resection from the terminal ileum to the splenic flexura was performed and an ileostomy was opened. Histopathological examination revealed high-grade B-cell lymphoproliferative disease. The patient died on the 6th postoperative day.In conclusion, although rarely seen, PGIS lymphoma should be kept in mind when diagnosing patients who present with GIS symptoms. © Logos Medical Publishing. All rights reserved.
Perfore primer intestinal lenfoma: Olgu sunumu
Keywords: Child; Intestinal lymphoma; Perforation; Surgery